Efektivitas Model Pembelajaran Problem Based Learning pada Materi Asam Basa Untuk Meningkatkan Hasil Belajar Peserta Didik - Taty Sulastry*; Nur Afifah Rais; Netti Herawati (Universitas Syiah Kuala, 2023)
Students have not been able to distinguish the concept of acid-base, and have not been able to apply every formula in acid-base, thus making students less active, less able to explore their knowledge, express their ideas, so that students' creative thinking skills are low. To help students, a learning model is needed that uses real-world problems as a context for students to be active and creative in finding solutions and expressing ideas to solve these problems through scientific procedures. This study aims to determine the high effectiveness of the problem based learning model on student learning outcomes on acid-base matrri. This research was conducted at SMA Negeri 8 Pinrang in class XI IPA 1. Data collection was carried out using learning outcomes tests and observation sheets. Data were analyzed using descriptive analysis. Learning is said to be effective if the learning outcomes of students are at N-gain g 0.3 to 1.00. The results showed that the average value of normalized gain was 0.75 in the high category, so it can be concluded that the use of problem-based learning models is effective on the learning outcomes of students in class XI IPA 1 SMAN 8 Pinrang